How the digital economy can contribute to green manufacturing efficiency - Sun, Xiaoshu; Zhang, Wanyu; Kuang, Xianming (Frontiers in Environmental Science, 2024)
This study employs a factor input-output non-expectation SBM-DEM model to assess the green manufacturing efficiency of 273 prefecture-level and higher cities in China. The relationship between the digital economy and green manufacturing efficiency is analyzed based on this model. The rise of the digital economy is found to contribute to the increase in green manufacturing efficiency, albeit with a non-linear "inverted U-shaped" trend. At the same time, the current level of digital economy development is slowly improving but has not yet reached the inflection point of the "inverted U-shaped" curve, and digital economy development still has a positive impact on green manufacturing efficiency at the current level of development. Furthermore, government intervention is critical in moderating the inverted U-shaped link between the digital economy and green manufacturing efficiency, which has a major weakening effect.